O fórum das entidades representativas do ensino superior particular: um novo intelectual orgânico de base coletiva - BRITO, Ana Paula Batista da Silva (Universidade Federal do Pará, 2019)
This study aims to investigate the role of Private Higher Education Representative Entities Forum (PHEREF – in Portuguese: Fórum das Entidades Representativas do Ensino Superior Particular – FERESP), as a new organic intellectual and of collective basis, and also to investigate how FERESP, within the current process of financialization of the privatecommercial educational sector in Brazil, has contributed on favoring this sector in public policies for higher education. Specifically, it aims to identify the evolution of the business community in Brazil and its repercussions as great intellectuals of the sector, to analyze the performance of FERESP within the scope of the Parliament, the Ministry of Education and the National Education Council, and to analyze, through letters from the Forum, the conception of higher education that this intellectual defends and potential changes that are being incorporated in higher education in the country. This work is a bibliographic research and a documentary analysis made through letters from each annual national meeting of the Forum, through documents extracted from the official website of the entity, among other documents. This work uses a timeframe between 2008 and 2018, beginning with the creation of PHEREF, aiming to analyze its beginning and its modification propositions in Brazilian legislation. The dissertation shows that the Forum brings in its political constitution a new conception of higher education, aligned with privatist interests: an education conception reduced to teaching bias – being it quick, as a commodity –, which transforms it in a financial article. And that the Forum appears to exercise, as a political-business organization, a great representativeness around the new policies that concern higher education in Brazil. Then, the study suggests that PHEREF operate as an organic intellectual of collective basis since it is an entity that has been introducing the construction of a public policy agenda for higher education, with a view to favoring private institutions, especially the private-mercantile ones. And that builds, thus, the strengthening of the process of financialization. The research indicates that the logic of the Forum creation relates to an action in favor of bourgeois extraction of teaching, for the construction of an agenda of changes which are represented by lobbies. And it concludes that the Forum ends up subsuming the education into teaching turned to the job market.